Pengetahuan dan sikap keluarga terhadap faktor genetik pada diabetes melitus tipe II - FANNY HAFIFA; Br Sianturi, Amelia Samita; Sarip, Najwa; VIO JOANA SARI (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
This study aims to describe the relationship between genetic factors and lifestyle in the occurrence of Type 2 Diabetes Mellitus (T2DM), a metabolic disorder characterized by elevated blood glucose levels due to insulin resistance. The research employed a qualitative approach through an in-depth interview with a T2DM patient. The interview results revealed that genetic factors play a significant role in increasing disease risk, especially in individuals with a family history of diabetes. However, unhealthy lifestyle habits such as high sugar intake, lack of physical activity, and obesity accelerate the onset of symptoms in genetically predisposed individuals. The informant also experienced complications in the form of chronic wounds leading to amputation, reflecting the impact of hyperglycemia on the circulatory and peripheral nervous systems. After diagnosis, the patient showed positive behavioral changes, including dietary regulation, regular exercise, and adherence to metformin therapy. Furthermore, the patient’s awareness evolved into an educational role within the family, promoting intergenerational prevention efforts. These findings emphasize the importance of a holistic approach encompassing medical, behavioral, and educational aspects in managing T2DM. In conclusion, the interaction between hereditary and lifestyle factors is a major determinant in the development of T2DM, yet behavioral modification can improve quality of life and prevent further complications.